A ação contra hegemônica da sociedade envelhecida, para a garantia da reprodução social, através do empreendedorismo - Oliveira, José Bernardo Enéias de (2015)
The research project investigates a social phenomenon that presents itself today in various parts of the world: the aging associated with entrepreneurship and their transformations in emancipatory process. Our focus is Brazil, further in São Paulo-SP, it is both great diversity of migrants from various other locations, broadened the range to take senior status, the umbrella of behavior and social relations, in time and space and socio-economic dimension, with a range of development opportunities. It is important to do so, the scene of the hegemonic and contrahegemônica neoliberal globalization, parts of the capitalist system. The study seeks opportunities for the elderly to continue to play socially, through new forms of business, using alternative employment and production models, increasingly acquainting human potential, with knowledge and skills development, adapting to the environment . The line of research studies social, cultural and anthropological, referring to the analysis of demographic aging and proposing alternatives for the country, a capitalist approach to economic and public policy, can support the society that is aging in sharp speed, with the point main analysis of its action and its potential before the (re) socialization and life cycle. Presentation of the research aims, without losing the anthropological approach and sociologist, give theoretical support to Geronte process of adapting to social changes through their potential for autonomy, to freely manage your life and your own choices, with the chances of survival resulting from their entrepreneurship and emancipatory knowledge